A comparison of milestone-based and buyout options contracts for coordinating R&D partnerships - BHATTACHARYA, Shantanu (Institutional Knowledge at Singapore Management University, 2015)
We analyze optimal contractual arrangements in a bilateral research and development (R&D) partnership between a risk-averse provider that conducts early-stage research followed by a regulatory verification stage and a risk-neutral client that performs late-stage development activities, including production, distribution, and marketing. The problem is formulated as a sequential investment game with the client as the principal, where the investments are observable but not verifiable. The model captures the inherent incentive alignment problems of double-sided moral hazard, risk aversion, and holdup. We compare the efficacy of milestone-based options contracts and buyout options contracts from the client's perspective and identify conditions under which they attain the first-best outcome for the client. We find that milestone-based options contracts always attain the first-best outcome for the client when the provider has some bargaining power in renegotiation and identify their applicability to different R&D partnerships.